Eating Pattern and Characteristic of Hypertension Patient In The DPT of Dukupuntang Health Center, Cirebon District - Yulia Yulia; Wahyudin Wahyudin; Loura Weryco Latupeirissa (LPPM ITEKES Mahardika, 2020)
Hypertension is a persistent increase in blood pressure in the arteries, where the systolic blood pressure is equal to or greater than 140 mmHg and the diastolic blood pressure equal to or above 90 mmHg. The results of a preliminary study conducted by researchers for 7 days from February 1, 2019 to February 7, 2019, out of 25 hypertension sufferers, only 5 patients had normal blood pressure, this was because people with hypertension complained and asked what foods were allowed and what should not be consumed by people with hypertension. The purpose of this study was to determine the relationship between diet and respondent characteristics. This type of research used in this research was descriptive quantitative, with a cross sectional approach. The population in this study were patients with hypertension at the UPT Puskesmas DPT Dukupuntang in 2019. The sample size was 84 respondents using purposive sampling, patients who experienced hypertension complications were not respondents. The variables measured in this study were dietary patterns and respondent characteristics (age, gender, employment status). Diet questionnaires and observation sheets were used to record the characteristics of the respondents. Data analysis was performed using univariate analysis with percentage and bivariate analysis with chi square test. The results of this study explain the diet of respondents in the good category (29.80%), moderate (21.40%), less (48.80%). Most respondents were male (72.61%), the most age was ≥45 years (81.00%), most of the respondents were still working (91.66%). There is a relationship between diet and respondent characteristics in hypertensive patients with a p value according to age 0.007, according to gender p value 0.002 and according to work p value 0.010. The conclusion of this study is that diet will be influenced by age, gender, occupation in people with hypertension